Evaluation of Housing Quality Indicators Using Analytic Network Process (ANP) - hossein mobarra; Mahsa Faramarzi Asli (تحقیقات کاربردی علوم جغرافیایی)
Housing is a crucial domain for testing human interactions and serves as a physical framework where social, cultural, and economic resources intertwine. In order to achieve social progress, the realm of housing encompasses not only the residential units themselves but also their surrounding environments. The focus on housing quality indicators is essential for attaining sustainable housing, which in turn lays the foundation for sustainable urban development. However, the increasing demand for housing and the prevailing quantitative approach have led to the neglect of the fundamental issue of housing quality in its true essence. Insufficient access to suitable housing can contribute to or worsen various psychological and social challenges. Hence, this research aims to identify the main indicators and components of housing quality and prioritize them, assuming equal weighting of their influence. The research methodology employed in this study is practical in its objective and descriptive-analytical in its approach. To achieve the intended objective, the Analytic Network Process (ANP) model is utilized to determine the weight and prioritize each indicator and component of housing quality. Subsequently, after evaluating the indicators using the ANP model, the results indicate that among the examined indicators, housing facilities and amenities with  0.318, housing security with 0.218, housing comfort with 0.145, compatibility with complementary uses with 0.142, housing durability with 0.109, and housing climate adaptation with 0.065 have been assigned the highest weights, respectively.